Pelaksanaan Waris Masyarakat Suku Baduy Muslim Di Desa Kanekes Kecamatan Leuwidamar Kabupaten Lebak Provinsi Banten - Andreas, Ricco; Rahmi Ria, Wati; ., Kasmawati; K.Y, Ade Oktariatas; Bahrudin, Muhammad (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2021)
The Muslim Baduy community adheres to the customs and traditions they profess from their ancestors. The inheritance system used in the Baduy customary inheritance uses the Bilateral system, which is that the mother and father are equally strong. Issues that will be discussed are how the implementation of the inheritance of the Baduy Muslim tribe. This type of research used in this study is empirical normative legal research, with exposure to data used primary and secondary data and analyzed qualitatively. The difference between Baduy inheritance law and Islamic inheritance law in Pikukuh as an unwritten inheritance rule in Islamic inheritance law is based on the Koran and As-Sunnah. There are similarities that the heirs are the descendants of the deceased and the inheritance can only be distributed after the death of the testator, but the Baduy community does not distribute the inheritance to the lineage to the top.